Addition of 2-deoxy-d-ribose to clinically used alginate dressings stimulates angiogenesis and accelerates wound healing in diabetic rats. (October 2019) - Azam, Maryam; Dikici, Serkan; Roman, Sabiniano; Mehmood, Azra; Chaudhry, Aqif A; U Rehman, Ihtesham; MacNeil, Sheila; Yar, Muhammad
Following recent work from our group on a small ribose-derived sugar 2-deoxy-d -ribose which stimulates angiogenesis in a chick chorionic allantoic membrane bioassay and in skin wounds in healthy rats, we tested the effect of this sugar when added to a common alginate wound dressing in a well-accepted diabetic skin wound model in rats. Dressings were simply loaded with filter-sterilized sugar solutions that were proved stable at room temperature for at least two weeks. Prior to undertaking the animal study, we assessed in vitro release of sugar loaded from alginate dressings loaded with either 5 or 10% 2-deoxy-d -ribose. Both showed more than 90% release of sugar over three days followed by a lesser and sustained release for up to eight days. Diabetes was induced in rats by streptozotocin injection followed by confirmation through measuring elevated blood glucose levels all over the period of the study. Full thickness skin wounds of 20 mm diameter showed slow healing and were still unhealed at 20th day in the control animals. The addition of alginate hydrogel did significantly stimulate wound healing compared to the untreated animals, but the addition of 2-deoxy-d -ribose at either 5 or 10% further and significantly improved the rate of wound healing. The most striking result was seen in the effect of sugar on angiogenesis in the wound beds where alginate alone did not improve the extent of CD34 identified blood vessels in the wound beds but the addition of sugar significantly increased these – this could be seen as early as seven days post addition of the sugar-loaded alginate dressing and was still evident at day 20. Thus, these results suggest that the controlled use of 2-deoxy-d -ribose could be a novel and cost-effective therapy for the management of impaired wound healing in diabetic patients.